Role of potassium channels in chlorogenic acid-induced apoptotic volume decrease and cell cycle arrest in Candida albicans - Yun, JiEun; Lee, Dong Gun (Biochimica et biophysica acta. General subjects, 2017)
Chlorogenic acid (CRA) is an abundant phenolic compound in the human diet. CRA has a potent antifungal effect, inducing cell death in Candida albicans. However, there are no further studies to investigate the antifungal mechanism of CRA, associated with ion channels. To evaluate the inhibitory effects on CRA-induced cell death, C. albicans cells were pretreated with potassium and chloride channel blockers, separately. Flow cytometry was carried out to detect several hallmarks of apoptosis, such as cell cycle arrest, caspase activation, and DNA fragmentation, after staining of the cells with SYTOX green, FITC-VAD-FMK, and TUNEL. CRA caused excessive potassium efflux, and an apoptotic volume decrease (AVD) was observed. This change, in turn, induced cytosolic calcium uptake and cell cycle arrest in C. albicans. Moreover, CRA induced caspase activation and DNA fragmentation, which are considered apoptotic markers. In contrast, the potassium efflux and proapoptotic changes were inhibited when potassium channels were blocked, whereas there was no inhibitory effect when chloride channels were blocked. CRA induces potassium efflux, leading to AVD and G2/M cell cycle arrest in C. albicans. Therefore, potassium efflux via potassium channels regulates the CRA-induced apoptosis, stimulating several apoptotic processes. This study improves the understanding of the antifungal mechanism of CRA and its association with ion homeostasis, thereby pointing to a role of potassium channels in CRA-induced apoptosis. •Chlorogenic acid (CRA) induces apoptosis in Candida albicans.•CRA induces potassium efflux leading to apoptotic volume decrease.•Block of the potassium channels inhibits the apoptotic effect of CRA.•Potassium channels play a key role in regulation of the CRA-induced apoptosis.